2014
DOI: 10.1111/joim.12276
|View full text |Cite
|
Sign up to set email alerts
|

High‐mobility group box‐1 in sterile inflammation

Abstract: Abstract. Tsung A, Tohme S, Billiar TR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
173
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 194 publications
(277 reference statements)
1
173
0
1
Order By: Relevance
“…We show here that HMGB1 is released by neutrophils during degranulation and that HMGB1 is postulated to assist in the recognition of extracellular DNA by intracellular TLR9 to activate the protumorigenic pathways (30,31). In addition, we, among others, have shown that HMGB1 is implicated in nearly every step of tumor progression (24,41,42). In addition to HMGB1, other peptides released during NETosis may play a role in tumor progression.…”
Section: Discussionmentioning
confidence: 95%
“…We show here that HMGB1 is released by neutrophils during degranulation and that HMGB1 is postulated to assist in the recognition of extracellular DNA by intracellular TLR9 to activate the protumorigenic pathways (30,31). In addition, we, among others, have shown that HMGB1 is implicated in nearly every step of tumor progression (24,41,42). In addition to HMGB1, other peptides released during NETosis may play a role in tumor progression.…”
Section: Discussionmentioning
confidence: 95%
“…hypoxia, senescence and autoimmune disease). The latter happens immediately (Scaffidi et al 2002), whereas the former is a slower mechanism mediated by cellular signal transduction (Tsung et al 2014). Once HMGB1 accumulates in the extracellular milieu, it conveys danger signals by triggering inflammatory pathways, including NF-κB, ERK and p38, in neighboring cells via numerous cell surface receptors such as TLRs 2, 4 and 9; RAGE; CD24; and others (Venereau et al 2013).…”
Section: Hmgb1mentioning
confidence: 99%
“…Of interest, HMGB1 has also been shown to form complexes with many pro-inflammatory mediators and enhance their respective actions in a synergistic manner (Hreggvidsdottir et al 2009). Furthermore, HMGB1 levels are elevated in multiple animal models of sterile injurious events (Tsung et al 2014) and in humans with acute organ injury, autoimmune diseases or cancer (Tong et al 2011. In vitro and in vivo, HMGB1 administration induces inflammation (Yang et al 2005), and more importantly, HMGB1 antagonism protects against sepsis (Yang et al 2004).…”
Section: Hmgb1mentioning
confidence: 99%
“…However, being released to extracellular milieu, HMGB1 could bind with its special receptor, TLR4, and exert as a central factor and prompt inflammatory responses during various pathophysiological processes. 17,18) Considering that HMGB1 plays important roles during development of inflammatory responses, researchers have tested whether HMGB1 neutralizing antibody could have beneficial effects on hemorrhagic shock. In their study, they showed that Neutralizing HMGB1 method was also demonstrated to ameliorate gut barrier dysfunction, elevate survival, and attenuate hemorrhagic shock significantly.…”
Section: Treatment Of Anti-hmgb1 Antibody Decreased Lps Induced Inflamentioning
confidence: 99%